Review and Analysis of the Anti-Sexual Harassment Policies and Procedures in Nippon Yusen Kaisha (NYK) For the Protection of Female Seafarers - Abella, Geoffrey (Future Science / FSH-PH Publications, 2025)
This study reviewed and analyzed the anti-sexual harassment policies and procedures of NYK-Fil Ship Management, focusing on the protection of female seafarers. Using a mixed-methods design, the research gathered quantitative data from a descriptive survey and qualitative insights from interviews with NYK-Fil office personnel and representatives from other manning agencies. Findings revealed that awareness of anti-sexual harassment policies among NYK-Fil seafarers is high, with no significant differences across age, rank, or experience. However, the interviews pointed out ongoing challenges, including fear of retaliation, cultural issues onboard, and gaps in leadership accountability. While NYK-Fil’s policies align with the requirements of Republic Act 12021 (Magna Carta for Seafarers), the study highlighted areas for improvement, including clearer communication, inclusive policy enhancements, and stronger leadership accountability. The findings suggest that awareness alone is insufficient; lasting protection depends on consistent enforcement and cultural transformation within the industry to fully protect all seafarers.